An innovative technique to restore velopharyngeal incompetency for a patient with cleft lip and palate - Ahmad, Manawar (BMJ Publishing Group, 2013)
Treatment of cleft lip and palate patients often demand well-coordinated work of medical and dental specialists. In spite of surgical and orthodontic therapy, prosthetic rehabilitation is always necessary because of partial anadontia, maxillary hypoplasia and velopharyngeal dysfuction. The aim of the prosthetic treatment is to improve aesthetics, function and speech of the patients; however, factors like underdeveloped and collapsed maxillary arch, retrognathic maxilla and reduced alveolar ridge height make the treatment challenging. This clinical report describes an interdisciplinary approach for the management of cleft lip and palate patient associated with mutilated dentition. The prosthetic phase began along with orthodontic treatment to achieve sufficient space distribution, which was restored with fixed dental prosthesis to stabilise the achieved status of occlusion. Palatal lift prosthesis was fabricated to restore the velopharyngeal incompetency with an innovative technique using ‘standard orthodontic expansion screw’ to eliminate hypernasality, decrease intelligibility of speech and to aid in deglutition.